From craft to profession : the practice of architecture in nineteenth-century America - Woods, Mary N., 1950- (University of California Press, 1999)
"This is the first in-depth study of the professionalization of architecture in nineteenth-century America. Mary Woods dispels the prevailing misunderstanding that the profession developed under the leadership of men formally schooled in architecture as an art during the late nineteenth century. Her archival research has uncovered many earlier manifestations of a professional practice whose first exemplars were men trained in building workshops or architectural offices during the early 1800s. While struggling to survive as designers and supervisors of construction projects, these men organized professional societies and worked for architectural education as well as for appropriate compensation and accreditation. They devised new forms of practice, like partnerships and large private offices, in the decades from 1820 to 1860. Although Woods looks at the contributions of such leading architectural practitioners as B. Henry Latrobe, Alexander J. Davis, H.H. Richardson, Louis Sullivan, and Stanford White, their role in her account is not that of inspired creators but that of collaborators, partners, merchandisers, educators, and lobbyists. She also looks at the less familiar contributions of women architects as well as those of African American, regional, and even failed practitioners."--Jacket.